Illocutionary Acts In The 1st 2023 Indonesian Presidential Candidate Debate By Prabowo Subianto: A Pragmatic Analysis - Lestary Jungjunan Effendy; Ervina CM Simatupang (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
This study investigates the illocutionary acts used by Prabowo Subianto during the first 2023 Indonesian presidential candidate debate. By conducting a pragmatic analysis, the research identifies and categorizes the types, functions, and strategies of Prabowo's speech acts, offering a comprehensive understanding of his communication approach and rhetorical effectiveness. Utilizing a qualitative-descriptive method, the debate was transcribed and analyzed to uncover the various illocutionary acts.The results reveal that Prabowo frequently uses assertives, directives, commissives, and expressives, each serving functions such as competitive, convivial, collaborative, and conflictive purposes. . In total, there are 30 data collected from the data source. The collected data were then classified based on 10 assertives, 4 directives, 6 commissives, 5 expressives, and 5 declarations. This study underscores the importance of understanding pragmatic elements in political communication, illustrating how Prabowo's assertive and often provocative statements aim to persuade, inform, and engage the audience, thereby influencing voter perceptions and decision-making. Through this analysis, the research provides a deeper insight into the role of illocutionary acts in political discourse and their impact on electoral outcomes, highlighting Prabowo's adept use of language to achieve his communicative goals.